Facial morphometric differences across face databases: influence of ethnicities and sex - Monteiro, Luis Carlos Pereira; Ripardo, Rachel Coelho; Torro-Alves, Nelson; Souza, Givago Silva (Frontiers in Neuroscience, 2023)
The scientific need for standardized, high-quality face stimuli has driven the creation of several face image databases in recent years. Such stimuli are especially important in facial asymmetry research. However, previous studies have reported facial anthropometric differences among a variety of ethnicities. It highlights the need to investigate whether these differences can also affect the use of facial image databases and particularly facial asymmetry research. In this work, we investigate facial asymmetry-based morphometric differences between the multi-ethnic Chicago Face Database (CFD) and the LACOP Face Database, composed of Brazilian subjects. Reliable differences in facial asymmetry were found between the two databases regarding ethnic groups. Eyes and mouth asymmetry seem to drive these differences. The asymmetry-based morphometrics differences among databases and ethnicities found in this study reinforce the necessity of creating multi-ethnic face databases.